Пошаговое объяснение:
12) а) (2у-1)/3+(у+1)/3>0 Умножим обе части неравенства на 3.
(2у-1)+(у+1)>0; 2у-1+у+1>0; 3у>0; у>0.
ответ: у∈(0;+∞).
б) (2х-1)/2-(1+х)/3<0; Умножим обе части неравенства на 6.
3(2х-1)-2(1+х)<0; 6х-3-2-2х<0; 4х<5; х<5/4; х<1,25.
ответ: х∈(-∞;1,25).
13) а) 3-(5-2х)<6; 3-5+2х<6; 2х<6+2; 2х<8; х<4.
ответ: 3.
б) 4(3-у)<14,6-2у; 12-4у<14,6-2у; -4у+2у<14,6-12; -2у<2,6; у>-1,3.
ответ: -1.
ответ:1)~ (3a-1)^3-27a^3+5=(3a-1)^3-(3a)^3+5=(3a-1-3a)\cdot\\ \\ \cdot((3a-1)^2+3a\cdot(3a-1)+(3a)^2)+5=-(9a^2-6a+9a^2+1+9a^2-3a)+\\ \\ +5=-27a^2+9a+4
Если а=-1, то -27a^2+9a+4=-27\cdot(-1)^2+9\cdot(-1)+4=-32
Если а=0, то -27a^2+9a+4=-27\cdot0^2+9\cdot0+4=4
Если а=1, то -27a^2+9a+4=-27\cdot1^2+9\cdot1+4=-14
2)~ (0.7b-2)^3-(0.7b+2)^3=(0.7b-2-0.7b-2)((0.7b-2)^2+\\ \\ +(0.7b-2)(0.7b+2)+(0.7b+2)^2)=-4(0.49b^2-2.8b+4+0.49b^2-\\ \\ -4+0.49b^2+2.8b+4)=-4(1.47b^2+4)=-5.88b^2-16
Если а=-2, то -5.88b^2-16=-5.88\cdot(-2)^2-16=-39.52
Если а=-1, то -5.88b^2-16=-5.88\cdot(-1)^2-16=-21.88
Если а=1, то -5.88b^2-16=-5.88\cdot1^2-16=-21.88
(5x-4)^3+(5x-2)^3-250x^3=125x^3-300x^2+240x-64+125x^3-\\ \\ -150x^2+60x-8-250x^3=-450x^2+300x-72
Если x=0.5, то -450x^2+300x-72=-450\cdot0.5^2+300\cdot0.5-72=-147
Если x=0, то -450x^2+300x-72=-450\cdot0^2+300\cdot0-72=-72
(0.2+5y)^3-(0.5+2y)^3-117y^3=125y^3+15y^2+0.6y+0.008-8y^3-\\ \\ -6y^2-1.5y-0.125-117y^3=9y^2-0.9y-0.117
Если y=-1, то 9y^2-0.9y-0.117=9\cdot(-1)^2-0.9\cdot(-1)-0.117=9.783
Пошаговое объяснение: